PENILAIAN IDEAL DAN EVALUASI EFEKTIF DALAM PEMBELAJARAN BAHASA ARAB - Mahmudah, Mahmudah; Susilo, Agus (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Assessment and evaluation in Arabic language teaching are essential components that determine the success of the learning process. This article discusses various types of assessment and evaluation that can be applied, including formative, summative, and authentic assessments. Formative assessment is conducted to provide feedback during the learning process, while summative assessment is performed to assess overall student achievement at the end of a learning period. Authentic assessment evaluates students’ abilities in real-life contexts. The article also highlights principles of fair and comprehensive assessment, such as validity, reliability, fairness, transparency, and alignment with learning objectives. Furthermore, it discusses steps in developing valid and reliable assessment instruments, from setting assessment goals to testing and revising instruments. By understanding various types of assessment, applying principles of fair assessment, and developing valid and reliable instruments, teachers can ensure that assessments provide an accurate portrayal of students’ abilities. This, in turn, will help students achieve their learning goals and enhance the overall quality of language learning